Improving Grid Resilience Using XG Boost Classifier in Smart Grid System - Patan Ameera Bakshu; Dr. K. Venkataramana (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Smart grids now integrate new devices to monitor the real-time conditions under electricity power companies. These technological systems leverage Artificial Intelligence (AI) and data analytics to support power companies with possible new ways toward realtime monitoring, control, and optimization of electricity grids. Such grids can respond to variations in power demand, contain renewable generation sources, and solve issues like energy conservation and cost reduction. These grids thus allow for direct generation of data for faster identification of faults, enabling many aspects such as improved load management and predictive maintenance, which reduces downtime and service interruptions. The smart meter also gives detailed information to customers on energy consumption patterns and behaviors as well as enhances customer engagement toward energy conservation. Customers then receive handy electricity services, with reliability on billing and possible cost savings from programs that induce demand response for the use of energy during off-peak hours. Furthermore, these systems will contribute to reducing carbon emissions and making the transition to cleaner and sustainable energy systems much easier. Of course, the most outstanding contribution toward these smart systems will be by governments, energy providers, and technology developers because despite all the advantages, some of the disadvantages are of enormous investment that these technologies require, along with cybersecurity threats and highly complex integration considerations when introducing them into the existing infrastructure. All these would require concerted efforts by government bodies, energy providers, and technology developers to overcome hurdles and focus on regulatory frameworks that ensure fair distribution of the benefits. Adopting smart systems in the electricity generation industry is an integral part of an energy future that is efficient, resilient, and sustainable. Smart technologies have changed massively how electricity is produced, distributed, and consumed advantageously for both providers and end-users while also supporting everyone’s global sustainability goals.